2022
DOI: 10.1038/s41597-022-01369-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-verified database of notable people, 3500BC-2018AD

Abstract: A new strand of literature aims at building the most comprehensive and accurate database of notable individuals. We collect a massive amount of data from various editions of and . Using deduplication techniques over these partially overlapping sources, we cross-verify each retrieved information. For some variables, adds 15% more information when missing in . We find very few errors in the part of the database that contains the most documented individuals but nontrivial error rates in the bottom of the notabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[13] A cross-database of notable people grouped into occupational domains showed that the four most popular are, in decreasing order: culture (30.6%), sports/games (27.7%), leadership (27.0%), and discovery/science (11.9%). [14] The above results are a plausible explanation for why our study among 42 notable people identifies actors, athletes, and musicians were the most reported profession. Regardless of their occupation, when a notable person becomes affected by a disease the public interest in the health issue may arise.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation

Head and Neck Cancer in Pan-American Notable People: An International Survey

Martínez-Ramírez,
Saldivia-Siracusa,
Pérez-de-Oliveira
et al. 2023
Preprint
“…[13] A cross-database of notable people grouped into occupational domains showed that the four most popular are, in decreasing order: culture (30.6%), sports/games (27.7%), leadership (27.0%), and discovery/science (11.9%). [14] The above results are a plausible explanation for why our study among 42 notable people identifies actors, athletes, and musicians were the most reported profession. Regardless of their occupation, when a notable person becomes affected by a disease the public interest in the health issue may arise.…”
Section: Discussionmentioning
confidence: 55%
“…[13] Celebrities (also known as notable people) are usually individuals with some notability index and influence on their field of activity. [14] They often emerge from the entertainment and sports industries, but different professions also have the power to influence a large number of people [13] and this wide recognition may be used to promote more publicity about the risk factors, signs, and symptoms of HNC. [15] Therefore, understanding the relevance of notable people and their potential influence on public interest in health issues such as HNC is extremely important.…”
Section: Introductionmentioning
confidence: 99%

Head and Neck Cancer in Pan-American Notable People: An International Survey

Martínez-Ramírez,
Saldivia-Siracusa,
Pérez-de-Oliveira
et al. 2023
Preprint
“…To collect the datasets, we used a top-down approach based on Wikipedia categories (Laouenan et al, 2022 ). First, we manually identified all the relevant Wikipedia categories (for instance, ‘eighteenth century Italian mathematicians’).…”
Section: Methodsmentioning
confidence: 99%
“…Leveraging the potential of Wikidata, Laouenan et al . (2022) focus on studying different intersectionalities, specifically, they aim to construct a comprehensive and accurate database of notable individuals by cross-verifying the information from various editions of Wikipedia and Wikidata, focusing on specific social science questions about gender, economic growth, urban and cultural development.…”
Section: Literature Reviewmentioning
confidence: 99%